The Dorsal Medial Prefrontal Cortex Is Recruited by High Construal of Non-social Stimuli - Baetens, Kris L. M. R.; Ma, Ning; Van Overwalle, Frank (Frontiers in Behavioral Neuroscience, 2017)
The dorsomedial prefrontal cortex (dmPFC) is part of the mentalizing network, a set of brain regions consistently engaged in inferring mental states. However, its precise function in this network remains unclear. It has recently been proposed that the dmPFC is involved in high-level abstract (i.e., categorical) identification or construction of both social and non-social stimuli, referred to as “high construal”. This was based on the observation of greater activation in the dmPFC shared by a high construal social condition (trait inference based on visually presented behavior) and a high construal non-social condition (categorization of visually presented objects) versus matched low construal conditions (visual description of the same pictures). However, dmPFC activation has been related to task contexts requiring responses based on self-guided generation of mental content or decisions as compared to responses more directly determined by the experimental context (e.g., free versus rule-governed choice). The previously reported dmPFC activity may reflect differences in task constraint (i.e., the extent to which the task context guided the process) confounded with the construal manipulation. Therefore, in the present study, we manipulated construal level and constraint independently, while participants underwent functional magnetic resonance imaging (fMRI). As before, participants visually described (low level construal) or categorized (high level construal) pictures of objects. Orthogonal to this, the description or categorization task had to be performed on either one object (low constraint) or on two objects simultaneously (high constraint), limiting the number of possible responses. Statistical analysis revealed common greater activation in both high construal conditions (high and low constraint) than in their low construal counterparts, replicating the influence of construal level on dmPFC activation (greater involvement in high than low construal), but no influence of constraint. In line with previous proposals and earlier work, we suggest that the dmPFC is involved in high-construal abstraction across different domains.